2004
DOI: 10.1097/01.ta.0000130761.78627.10
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Renal Failure in Patients with Rhabdomyolysis: Do Bicarbonate and Mannitol Make a Difference?

Abstract: Abnormal CK levels are common among critically injured patients, and a CK level greater than 5,000 U/L is associated with RF. BIC/MAN does not prevent RF, dialysis, or mortality in patients with creatine kinase levels greater than 5,000 U/L. The standard of administering BIC/MAN to patients with post-traumatic rhabdomyolysis should be reevaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
211
2
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(227 citation statements)
references
References 16 publications
5
211
2
9
Order By: Relevance
“…42 Unfortunately, the use of sodium bicarbonate has not been shown to decrease the incidence of AKI or mortality in rhabdomyolsis. 43 Even though questions also remain about its efficacy, mannitol was selected for this patient due to its ability to increase renal blood flow and maintain renal filtration fraction and oxygenation. 43,44 Veno-venous extracorporeal membrane oxygenation was considered briefly on POD 3 due to profound hypoxemia and refractory hypercarbia but ultimately was not necessary, given the rapid improvement in his respiratory status after diuresis was initiated.…”
Section: Postoperative Intensive Care Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Unfortunately, the use of sodium bicarbonate has not been shown to decrease the incidence of AKI or mortality in rhabdomyolsis. 43 Even though questions also remain about its efficacy, mannitol was selected for this patient due to its ability to increase renal blood flow and maintain renal filtration fraction and oxygenation. 43,44 Veno-venous extracorporeal membrane oxygenation was considered briefly on POD 3 due to profound hypoxemia and refractory hypercarbia but ultimately was not necessary, given the rapid improvement in his respiratory status after diuresis was initiated.…”
Section: Postoperative Intensive Care Managementmentioning
confidence: 99%
“…43 Even though questions also remain about its efficacy, mannitol was selected for this patient due to its ability to increase renal blood flow and maintain renal filtration fraction and oxygenation. 43,44 Veno-venous extracorporeal membrane oxygenation was considered briefly on POD 3 due to profound hypoxemia and refractory hypercarbia but ultimately was not necessary, given the rapid improvement in his respiratory status after diuresis was initiated. Fortunately, his rhabdomyolysis and renal failure resolved, allowing for rapid ventilator weaning, successful extubation, and subsequent recovery.…”
Section: Postoperative Intensive Care Managementmentioning
confidence: 99%
“…Retrospective cohort analyses suggested that intravenous sodium bicarbonate was associated with an increased risk of CIN [43] or pigment nephropathy [44,45]. The multicenter trial of prophylactic perioperative sodium bicarbonate administration to prevent AKI following open heart surgery found a non-significant increase in AKI and a possible increase in in-hospital mortality [37].…”
Section: Prevention Of Aki By Sodium Bicarbonate Infusion: Harmsmentioning
confidence: 99%
“…Despite these theoretical benefits, the use of sodium bicarbonate does not appear to prevent renal failure, the need for dialysis, or mortality in patients with rhabdomyolysis [61]. Similarly, the use of mannitol or loop diuretics to increase urinary flow offers the theoretical benefit of decreasing the concentration of myoglobin in the renal tubules, however, clinical studies have failed to show benefit from their administration [60,61].…”
Section: What Treatments Should Be Undertaken In a Patient With Rhabdmentioning
confidence: 99%